How to Develop Ecotourism in Ijen Banyuwangi Crater ? - Widowati, Sri; Suryawan Wiranatha, Agung; Bagus Suryawan, Ida (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Tourism is an important part in supporting the development of social, economic, cultural, and even regional political life. Ijen Crater is listed as the largest crater in the world and one of the tourism industries in Banyuwangi City with high tourism potential in the East Java region, Indonesia. The purpose of this study is to find the right formula to develop ijen crater tourism and maintain nature conservation. The research method uses the AHP (Analytic Hierarchy Process) approach. The results of the analysis obtained that cooperation strategies with stakeholders 0.37%, community empowerment strategies 0.315%, regulatory improvement strategies 0.186% and management management strategies 0.129%. Stakeholder cooperation is an important priority because it is useful to be able to create relationships by building good communication in running the wheels of the ecotourism industry. This study can ultimately be useful for mapping strategies in developing ecotourism in Ijen Crater, Tamansari Village, Banyuwangi, Indonesia.